Antibody-Dependent Cellular Phagocytosis of HIV-1-Infected Cells Is Efficiently Triggered by IgA Targeting HIV-1 Envelope Subunit gp41 - Duchemin, Maxence; Tudor, Daniela; Cottignies-Calamarte, Andréa; Bomsel, Morgane (Frontiers in Immunology, 2020)
Abstract Antibodies mediate a broad array of non-neutralizing Fc-mediated functions against HIV-1 including antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP). Accordingly, ADCC and ADCP induced by anti-HIV envelope gp120 IgG have been correlated to the limited success of the HIV-1 phase III vaccine trial RV144. It remains elusive whether ADCP can also be triggered by IgA, the isotype predominant at mucosal surfaces through which HIV-1 is mainly transmitted. Yet, we have previously shown that the HIV envelope subunit gp41-specific broadly neutralizing antibody 2F5 under the IgA isotype (2F5-IgA) triggers ADCC and cooperates with 2F5-IgG to increase HIV-1-infected cell lysis. Here, we now demonstrate that 2F5-IgA, more efficiently than 2F5-IgG, induces ADCP not only of gp41-coated beads but also of primary HIV-1-infected cells in a FcαRI-dependent manner. Both primary monocytes and neutrophils can act as effector cells of 2F5-IgA-mediated ADCP, although with different kinetics with faster neutrophil phagocytosis. However, unlike for ADCC, 2F5-IgA and 2F5-IgG do not cooperate to increase ADCP. Altogether, our results reveal that gp41-specific IgA mediate the efficient phagocytosis of HIV-1-infected cells. Inducing such ADCC and ADCP-prone IgA response by vaccination in addition to anti-HIV envelope IgG, might increase the protection again HIV acquisition at mucosal level.